Preliminary Biocompatibility Tests of Poly-ε-Caprolactone/Silver Nanofibers in Wistar Rats - Álvarez-Ortega, Oskar; Ruiz-Ramírez, Luis Roberto; Garibay-Alvarado, Jesús Alberto; Donohue-Cornejo, Alejandro; Espinosa-Cristóbal, León Francisco; Cuevas-González, Juan Carlos; Reyes-López, Simón Yobanny (Polymers, 2021)
Currently, nanotechnology is perceived as a promising science that produces materials with diverse unique properties at a nanometric scale. Biocompatibility tests of poly-ε-caprolactone nanofibers, embedded with silver nanoparticles manufactured by means of the electrospinning technique, were carried out in Wistar rats to be used as oral dressings for the eradication of bacteria. Solutions of 12.5, 25, 50 and 100 mM of silver nitrate were made using N-dimethylformamide (DMF) and tetrahydrofuran (THF) as reducing solvents with 8% of poly-ε-caprolactone (PCL) polymer. The solutions were electrospun, and the nanofibers obtained in the process were characterized by infrared spectroscopy, Raman spectroscopy, dark field optical microscopy, scanning electron microscopy and X-ray scattering spectroscopy. The nanofibers had an average diameter of 400 ± 100 nm. Once the characterization of the material was done, three implants of each concentration of the nanofibers were formed and placed in the subcutaneous tissue of the rats. Three experimental subjects were used, leaving the material in them for a length of two, four and six weeks, respectively. The rats showed good healing, with the lesions completely healed at four weeks after implantation. After that time, biopsies were taken, and histopathological sections were made to evaluate the inflammatory infiltrate. The tissues of the rats presented chronic inflammatory infiltrate composed mainly of lymphocytes and giant multinucleated cells. The material was rejected by the rats when a layer of collagen and fibroblasts was produced, coating the material, a process characteristic of a foreign body reaction.